Relação ecológica entre as comunidades fitoplanctônica e zooplanctônica em reservatório eutrofizado durante período de pluviosidade atípica - Câmara, Fabiana Rodrigues de Arruda (Universidade Federal de São Carlos, 2011)
The study of the plankton community provides better understanding of trophic relationships through their responses in relation to environmental variables of freshwater ecosystems. These responses include the organization of the structure and species composition both in spatial and temporal scale. The study much more important in water scarce northeast Brazil where reservoirs are the main source of potable water supply. This thesis examines aspects related to the ecological relationship between phytoplankton and zooplankton communities in a eutrophic reservoir of Rio Grande do Norte State. The study was conducted during a period significantly affected by climatic change as a consequence of La Niña event (2008-2009), causing heavy rainfall in certain regions. Samples were collected monthly in the Armando Ribeiro Gonçalves reservoir (ARG), Assu, RN, during two distinct phases: Hydrodynamic Instability ( I e II) and Stability. The seasonal relationships between phytoplankton and zooplankton communities were analyzed from the data of morpho functional species data, their biomass, composition, frequency, diversity, richness, evenness, and dominance index. These biotic variables are tested to environmental variables such as water temperature, transparency, turbidity, conductivity, pH and total and inorganic nutrients (nitrate-N, Nnitrite, ammonia-N and Soluble Reactive Phosphorus, total Nitrogen and Phosphorus), measured in situ or by spectrophotometric methods, according with specific methodologies. In addition to descriptive aspect, experimental approach was used to explain certain biotic relationship found in descriptive study. The results demonstrate significant environmental variations and planktonic compositional changes, which are mediated by hydrodynamic forces such as atypical high rainfall, greater influx of river water, water turbulence and complete mixture of water column and heavy nutrient suspension. Phytoplankton species composition was classified according to morphofunctional characteristic and the succession of phytoplankton revealed how the composition and density of cyanobacteria altered during stable and unstable periods. The results also showed considerable reduction in the cyanobacteria biomass and concomitant increase in phytoplankton diversity. During the second period of hydrodynamic instability of planktonic species composition was shifted in favour of predominant species of non-toxic cyanobacterial, followed by members of Chlorophytes and Bacilariophytes along with the higher biomass of copepod nauplii, juvenile copepods and Cladocera. The presence of Chlorophyte and Bacillariophyte species with juvenile copepods and cladoceran indicate the features of better water quality in the ARG reservoir. During the study, we observed a negative correlation between zooplankton groups and Ostracods Calonoid Copepods. The results indicate the predominance of Physiocypria schubarti (Ostracod) over subdued Notodiaptomus cearensis (Clanoid Copepod) in the midst of filamentous cyanobacteria suggesting a mere co-existence of species without competition for food. Moreover, the high abundance of Ostracods in the water column is not a relevant factor that determines a reduction in the biomass of Calanoid Copepods. On the other hand, we can infer that the toxicity of filamentous cyanobacteria may affect some individuals in the population of Calanoid Copepods.
Keywords: Ecologia de comunidades; Fitoplâncton; Zooplâncton; Água - qualidade; La Niña (corrente oceânica); Eutrofização; Phytoplankton; Zooplankton; Water quality; La Nina; Eutrophic; CIENCIAS BIOLOGICAS::ECOLOGIA